Microwave assisted transesterification of waste cooking oil using immobilized lipase enzyme - Shah, L. Amer; Jolius, Gimbun; S., Nurdin (2021)
This paper presents a microwave assisted transesterification of waste cooking oil using immobilized lipase enzyme. The commercially available immobilized lipase from Candida Rugosa was used. Comparisons with the ultrasonic assisted enzymatic transesterification are also made. Influence of methanol to oil ratio, temperature, mixing and reaction time to the methyl ester conversion were analysed in detail. The results suggest that microwave assisted enzymatic transesterification (MAET) is better (over 3.5 times higher methyl ester) than the ultrasonic assisted method (UAET). It was found that the optimum condition for MAET with 97.23% FMAE yield can be achieved at 4 hours, methanol to oil ratio of 6:1 and temperature of 40 °C. The biodiesel produced in this work is within the limits of specification described by ASTM D6751.